The evaluation of customer experience using BP neural network‐taking catering O2O takeout. (30th October 2019) - Pei, Yi‐Lei; Li, Dan‐Dan; Xue, Wan‐Xin
Summary: In China, catering O2O takeout develops rapidly; thus, there is the fierce competition in the catering O2O industry. More and more catering O2O takeout platforms focus on customer experience, especially service experience in distribution link, so it is extremely necessary to evaluate customer experience of catering O2O takeout in China scientifically and reasonably. This paper establishes a customer experience evaluation index system from the perspectives of O2O takeout platform, delivery staff, and distribution process. This paper uses the BP Neural Network Model to evaluate customer experience of catering O2O takeout, uses Principal Component Analysis to extract principal components as the input of BP neural network model, and uses the model of MATLAB Neural Network Toolbox to conduct the training simulation with customer experience data. The results show that the model can evaluate customer experience of catering O2O takeout. The analysis in this paper provides a new evaluation method of customer experience for catering O2O takeout in China.